Bilateral Proximal Tibial Sleeve Fractures in a Child: A Case Report - Williams, Daniel (Arch Trauma Res, 2015)
INTRODUCTION: A sleeve fracture classically describes an avulsion of cartilage or periosteum with or without osseous fragments and usually occurs at the inferior margin of the patella. Tibial tubercle sleeve fractures in the skeletally immature are extremely rare. CASE PRESENTATION: In this report the authors describe a 12-year-old boy with no systemic disease and no steroid use who sustained bilateral proximal tibial sleeve fractures whilst playing football. Both ruptures were associated with rupture of the medial patellofemoral ligament and tear of the medial retinaculum. Treatment was performed with primary end-to-end repair, reinforcement with bone anchors and cerclage wires with an excellent outcome. CONCLUSIONS: We feel this rare, currently unclassified variant of a tibial tubercle avulsion fracture should be recognised and consideration taken to adding it to existing classification systems.